The declaration of adoptability situation at a crossroads - Natalia de la Torre (Oñati Socio-Legal Series)
This paper investigates a topic that is booming in Argentine jurisprudence: the declaration of the adoptability situation of children based on the informed, thoughtful, and autonomous decision of their parents -generally women who decide not to exercise their maternity– to give their child for adoption considering the obligatory gender perspective, in line with the rights of children. With this objective as a goal, the regulation of the judicial declaration of the situation of adoptability and the autonomous decision to give a daughter or son for adoption is synthesized, the exception being that the declaration in a situation of adoptability is not appropriate if a referent of the family of origin or extended family is able to take care of the child and its complementarity with the best interest of the child. At the same time, the paths taken in Argentine jurisprudence regarding the birth of children after hindering the legal interruption of pregnancy are critically analyzed.